2015
DOI: 10.1371/journal.pone.0118759
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Protects against Isoproterenol-Induced Cardiac Hypertrophy by Regulating NF-κB/PGC-1α Signaling Mediated Energy Biosynthesis

Abstract: We previously reported that Astragaloside IV (ASIV), a major active constituent of Astragalus membranaceus (Fisch) Bge protects against cardiac hypertrophy in rats induced by isoproterenol (Iso), however the mechanism underlying the protection remains unknown. Dysfunction of cardiac energy biosynthesis contributes to the hypertrophy and Nuclear Factor κB (NF-κB)/Peroxisome Proliferator-Activated Receptor-γ Coactivator 1α (PGC-1α) signaling gets involved in the dysfunction. The present study was designed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 34 publications
2
50
0
1
Order By: Relevance
“…Our previous studies confirmed that AsIV can suppressmyocardial hypertrophy and attenuate apoptosis of hypertrophic cardiomyocyte Yang et al 2013;Zhang et al 2015), which may be partially due to its anti-oxidative, anti-inflammatory and anti-apoptotic activities that might be endothelium-protective under pathophysiological conditions. Previous study has been demonstrated that AsIV inhibits H 2 O 2 -induced HUVECs apoptosis by suppressing Nox4 expression (Ma et al 2015).…”
supporting
confidence: 73%
“…Our previous studies confirmed that AsIV can suppressmyocardial hypertrophy and attenuate apoptosis of hypertrophic cardiomyocyte Yang et al 2013;Zhang et al 2015), which may be partially due to its anti-oxidative, anti-inflammatory and anti-apoptotic activities that might be endothelium-protective under pathophysiological conditions. Previous study has been demonstrated that AsIV inhibits H 2 O 2 -induced HUVECs apoptosis by suppressing Nox4 expression (Ma et al 2015).…”
supporting
confidence: 73%
“…Previous studies have confirmed that AST-IV could reverse or delay cardiac remodeling caused by various reasons, such as viral infection [35], isoproterenol (ISO) [26, 31, 53] and lipopolysaccharide (LPS) [27]. AST-IV protected against ISO-induced cardiac hypertrophy via inhibiting p65 translocation and increasing PPARγ coactivator 1α (PGC-1α) [28]. TLR4/NF-small ka and Cyrillic B signaling pathways were the other targets for the effects of AST-IV against ISO-induced cardiac hypertrophy [26].…”
Section: Discussionmentioning
confidence: 99%
“…Over-stimulation of mTORC1 pathway through growth factors promoted cardiac senescence. Previous studies proved that AST-IV could resist the cardiac adrenergic [28] and angiotensin stimulation [56], inhibit mTORC1 [30], and thus protect against cardiac remodeling. In this study, we found that the hypercholesterolemic heart presented high expressions of p16 and p53, which could be reversed after AST-IV treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bunge, is one of the most widely used plant-derived drugs in traditional Chinese medicine for diabetes therapy (10). The saponin astragaloside IV has been reported to exert various pharmacological effects; astragaloside IV inhibited hepatic glycogen phosphorylase (GP) and glucose-6-phosphatase (G6P) activities thereby decreasing serum glucose levels in diabetic mice (12), attenuated lipolysis and reduced insulin resistance induced by tumor necrosis factor α (TNFα) in 3T3-L1 adipocytes (13), improved the symptoms of metabolic syndrome in fructose-fed rats (14), prevented human cardio vascular pathological changes and protected against cardiovascular injury in rats (15)(16)(17)(18) improved renal function (19)(20)(21)(22), reduced the progression of peripheral neuropathy (23), and attenuated inflammatory responses by suppressing the nuclear factor-κB (NF-κB) pathway (24)(25)(26). Xu et al (27) reported that other astragalosides, astragaloside II and isoastragaloside I, elevated serum levels of adiponectin and alleviated insulin resistance and glucose intolerance in obese mice.…”
Section: Introductionmentioning
confidence: 99%